(untitled) (Scientific journal of the Fergana State University, 2025)
This study analyzes the artistic interpretation of magical realism and hauntology elements in Stephen King’s novels «The Shining» and «Doctor Sleep.» The research explores the Overlook Hotel, its properties that disrupt the boundaries of time and reality, and its connection to human psychology and memory. «It» examines the cyclical movement of time, déjà vu, and hauntological phenomena, revealing how reality and illusion blend. The study also highlights the psychological crisis and the struggle with the unconscious through the characters of Jack Torrance and Danny Torrance.